Threshold Photoelectron Spectroscopy of IO and HOI. Issue 19 (11th September 2019) - Schleier, Domenik; Reusch, Engelbert; Lummel, Lisa; Hemberger, Patrick; Fischer, Ingo
Abstract: Iodine oxides appear as reactive intermediates in atmospheric chemistry. Here, we investigate IO and HOI by mass‐selective threshold photoelectron spectroscopy (ms‐TPES), using synchrotron radiation. IO and HOI are generated by photolyzing iodine in the presence of ozone. For both molecules, accurate ionization energies are determined, 9.71±0.02 eV for IO and 9.79±0.02 eV for HOI. The strong spin‐spin interaction in the 3 Σ − ground state of IO + leads to an energy splitting into the Ω=0 and Ω=±1 sublevels. Upon ionization, the I−O bond shortens significantly in both molecules; thus, a vibrational progression, assigned to the I−O stretch, is apparent in both spectra. Abstract : The reactive molecules IO and HOI are investigated by mass‐ selected threshold photoelectron spectroscopy using synchrotron radiation. The ionization energies, vibrational frequencies in the cations, and spin‐spin splitting in IO + are determined.